Assessing Marine Microbial Induced Corrosion at Santa Catalina Island, California - Ramírez, Gustavo A.; Hoffman, Colleen L.; Lee, Michael D.; Lesniewski, Ryan A.; Barco, Roman A.; Garber, Arkadiy; Toner, Brandy M.; Wheat, Charles G.; Edwards, Katrina J.; Orcutt, Beth N. (Frontiers in Microbiology, 2016)
High iron and eutrophic conditions are reported as environmental factors leading to accelerated low-water corrosion, an enhanced form of near-shore microbial-induced corrosion. To explore this hypothesis, we deployed flow-through colonization systems in laboratory-based aquarium tanks under a continuous flow of surface seawater from Santa Catalina Island, California, USA, for periods of two and six months. Substrates consisted of mild steel – a major constituent of maritime infrastructure – and the naturally occurring iron sulfide mineral pyrite. Four conditions were tested: free-venting “high-flux” conditions; a “stagnant” condition; an “active” flow-through condition with seawater slowly pumped over the substrates; and an “enrichment” condition where the slow pumping of seawater was supplemented with nutrient rich medium. Electron microscopy analyses of the two-month high flux incubations document coating of substrates with “twisted stalks”, resembling iron oxyhydroxide bioprecipitates made by marine neutrophilic Fe-oxidizing bacteria. Six-month incubations exhibit increased biofilm and substrate corrosion in the active flow and nutrient enriched conditions relative to the stagnant condition. A scarcity of twisted stalks was observed for all six month slow-flow conditions compared to the high-flux condition, which may be attributable to oxygen concentrations in the slow-flux conditions being prohibitively low for sustained growth of stalk-producing bacteria. All substrates developed microbial communities reflective of the original seawater input, as based on 16S rRNA gene sequencing. Deltaproteobacteria sequences increased in relative abundance in the active flow and nutrient enrichment conditions, whereas Gammaproteobacteria sequences were relatively more abundant in the stagnant condition. These results indicate that i) high-flux incubations with higher oxygen availability favor the development of biofilms with twisted stalks resembling those of marine neutrophilic Fe-oxidizing bacteria and ii) long-term nutrient stimulation results in substrate corrosion and biofilms with different bacterial community composition and structure relative to stagnant and non-nutritionally enhanced incubations. Similar microbial succession scenarios, involving increases in nutritional input leading to the proliferation of anaerobic iron and sulfur-cycling guilds, may occur at the nearby Port of Los Angeles and cause potential damage to maritime port infrastructure.